PERLINDUNGAN HUKUM TERHADAP MOTIF BATIK TULIS DI KOTA PANGKALPINANG - Bresnisya, Verani (PROGRESIF: Jurnal Hukum, 2016)
Legal protection is a legal action taken to protect the rights of members of the society, particularly in this case business owners in order to get benefit from the rights conferred by law. The handwritten batik discussed in this thesis has been developed by Batik Tulis Pinang Sirih business group since 9 months ago. The embrace the community to participate in preserving the culture that exists in the Bangka Belitung Islands. Currently they have legal protection for 5 (five) handwritten batik designs they have created. In this regard, the business has made efforts to protect the handwritten batik design by registering the handwritten batik design to get Industrial Design Rights. Based on this research, it is recommended to increase the legal protection for handwritten batik design by applying for a copyright.